Pembelajaran IPA Berbasis Problem Based Learning Untuk Siswa SDN 2 Cangkreplor - Alfirra Riznia Gisalsani; Andi Pratama; Desy Permata Hati (Indonesian Journal of Elementary and Childhood Education, 2024)
This research is motivated by the lack of availability of teaching materials that support project-based learning at the elementary school level. The purpose of this study is to describe the process of developing Teaching Materials Based on Problem Based Learning (PBL) which is designed to improve the creative, critical, and learning outcomes of grade IV elementary school students in science subjects. The method used is Research and Development with the Borg & Gall development model. The research was conducted at SDN 2 Cangkreplor with the subject of grade IV students. Data on the validity of teaching materials were obtained through interviews, observations, and simulations, while practicality data was collected using observation sheets and interviews with classroom teachers. The effectiveness of teaching materials is measured from learning activities and student learning outcomes. The results of the validity test show that the teaching materials are considered "very valid" by expert validators and practitioners. Data analysis is carried out in an inductive-qualitative manner with a focus on meaning rather than generalization. The results of the study show that PBL-based teaching materials that are integrated with the inquiry method for grade IV elementary school students are proven to be valid, practical, and effective.